Relationship Between Pregnant Woman's Knowledge Level About Maternal Nutritional And Gestational Weight Gain In Puskesmas Banjardawa - Yoga Gusthi Pangestu1; Trisha Alya Rahmi (Universitas Andalas, 2023)
Introduction: Gestational weight gain (GWG) is the weight gain of pregnant women duringpregnancy. Inadequate/excessive GWG can have an impact on fetal weight at birth. The 2019MCH handbook includes a gestational weight gain chart, but the method of calculating thebody mass index is not included so that there are difficulties in filling out the chart and GWGis not monitored.Aims: to examine the relationship between the level of nutritional knowledge of pregnantwomen and gestational weight gain.Methods: This research is an analytic observational with cross sectional method. Thisresearch was conducted in the working area of the UPT Puskesmas Banjardawa , namelyBanjaran Village, Banjardawa Village, Taman Village, Beji Village, and Pedurungan Villagein September - October 2022.Result: Most of the pregnant women in the Banjardawa Health Center working area in 2022were 26-35 years old, had low education level, middle to lower economic status, averagegestational age in the third trimester, and had no history of disease. Most pregnant women inthe working area of the Banjardawa Health Center in 2022 already have a good level ofknowledge about the nutrition of pregnant women, but have inappropriate gestational weightgain. The results of the bivariate analysis showed that there was no significant relationshipbetween the knowledge level of pregnant women and gestational weight gain in pregnantwomen.Conclusion : Health workers are expected to be able to provide motivation and informationabout nutrition for pregnant women to pregnant women, so that they are expected to helpwith appropriate gestational weight gain